2018
DOI: 10.1097/md.0000000000012885
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal thickness changes in non-treated acute and ranibizumab-treated chronic central serous chorioretinopathy

Abstract: To evaluate the changes in subfoveal retinal, and choroidal thicknesses (CT) in the non-treated acute and the ranibizumab-treated chronic central serous chorioretinopathy (CSCR) patients.This retrospective study included 32 eyes of 32 consecutive patients with CSCR. There were 12 patients who presented with a spontaneous resolution of CSCR (Group 1) and 20 patients who were treated with ranibizumab for persistent subretinal fluid (SRF) (Group 2). Optical coherence tomography (OCT) imaging of subfoveal retinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The efficacy of PDT for chronic CSC has been reported previously, however [ 2 , 3 , 11 ], and it is ethically challenging to follow up on chronic CSC without treatment. In addition, since the current results are relatively large compared to choroidal changes during spontaneous remission in acute CSC [ 35 , 36 ], we believe that the choroidal changes observed in this study were related to PDT.…”
Section: Discussionmentioning
confidence: 87%
“…The efficacy of PDT for chronic CSC has been reported previously, however [ 2 , 3 , 11 ], and it is ethically challenging to follow up on chronic CSC without treatment. In addition, since the current results are relatively large compared to choroidal changes during spontaneous remission in acute CSC [ 35 , 36 ], we believe that the choroidal changes observed in this study were related to PDT.…”
Section: Discussionmentioning
confidence: 87%
“…A total of 20 studies were included in this systematic review (n=339 eyes) 3–5 16 20 22–36. Twelve were prospective studies (n=165),3–5 22–25 29–32 34 seven were retrospective studies (n=173)16 26–28 33 35 36 and one was a case report (n=1) 20.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis was confirmed by recent studies, which found evidence of hyperpermeability from the choriocapillaris on Indocyanine green (ICG) angiography. If there is sufficient hydrostatic pressure from the choroidal vasculature causing leakage from RPE and serous retinal detachment [16]. SD-OCT studies of the RPE in CSC have shown RPE defects in the location of a fluorescein leakage in some patients [17].…”
Section: Joj Ophthalmology Discussionmentioning
confidence: 99%